MODEL PERENCANAAN EKONOMI MELALUI METODE PENGAMBILAN KEPUTUSAN DENGAN AHP (ANALYTIC HIERARCHY PROCESS) - Soebagiyo, Daryono (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2001)
The Analytic Hierarchy Process (AHP) is a decision and planning which has received a great deal of attention in the past few years from both prettiness of the art/science of planning, and from theoreticians interested in this innovative approach in planning.This paper it is shown that to demonstrated used a simulation analysis measurement involved in the AHPs theory the one of how to derive priority vectors from matrix ofpairwise comparisons has found an especially large interest. Following the concept, AHP server as framework for people to structure their own problem and provide judgements based on knowledge, season on felling, to derive a set of priorities considered as an optimal solution to decision problem.